Digital Forensic & Female: Unveiling Law Journal Insights (2012-2022) - Tertia Mukti, Artanti; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
In this data article, we conducted a comprehensive search on Lens.org using the keywords "Digital forensic" and "female" to gather a dataset of 6,280 documents. We refined our search by filtering for "journal articles," narrowing the date range to 2012-2022, and focusing on the subject matter "Law." This process yielded a dataset of 301 journal articles. The purpose of this data collection was to provide a valuable resource for researchers interested in the intersection of digital forensics and gender-related topics, facilitating easier access to relevant literature. The dataset serves as a rich source for future experiments and research, enabling scholars to explore and analyze the evolving landscape of digital forensics within the context of law and gender, ultimately contributing to a deeper understanding of this critical field. Highlights : Extensive Data Collection: Our study gathered 6,280 documents, offering a comprehensive dataset for researchers. Gender Focus: We honed in on the intersection of digital forensics and female representation. Valuable Resource: The dataset provides a rich source for future research in the field of law and gender. Keywords: Digital Forensic, Female Representation, Law Journals, Data Collection, Research Resource